Comparison of cytotoxicity, genotoxicity and immunological inflammatory biomarker activity of several endodontic sealers against immortalized human pulp cells - Martinho, F. C. [UNESP]; Camargo, S. E.A. [UNESP]; Fernandes, A. M.M. [UNESP]; Campos, M. S.; Prado, R. F. [UNESP]; Camargo, C. H.R. [UNESP]; Valera, M. C. [UNESP] (Wiley, 2018)
Aim: To establish an SV40 T-Ag-transfected cell line of human pulp-derived cells in order to compare the cytotoxicity, genotoxicity and to investigate the activities of immunological biomarkers of several endodontic sealers. Methodology: Primary human pulp cells and transfected cells were cultured. Cell morphology and proliferation were analysed, and the expression of cell-specific gene transcripts and proteins was detected by RT–PCR and immunohistochemistry. Transfection of human pulp-derived cells resulted in an immortalized cell line retaining phenotypic characteristics from the primarily cells tested. The SV40 T-Ag-transfected cells were cultured and stimulated by sealers (Apexit Plus, Real Seal, AH Plus, and EndoREZ) to evaluate the cytotoxicity and genotoxicity by MTT and MTN assays, respectively. Immunological inflammatory biomarkers (IL6, IL8 and TNF-α) were determined by ELISA assay. The differences between median values were statistically analysed using Kruskal–Wallis and Dunn's tests at 5% significance level. Results: The cytotoxicity assay revealed that multimethacrylate (Real Seal) was the most cytotoxic sealer (P < 0.05) and exhibited the highest inflammatory potential against the SV40 T-Ag-transfected cells (P < 0.05). All root canal sealers tested were able to stimulate the immortalized pulp cells to produce IL-6, IL-8 and TNF-α, with differences in relation to the control group (P < 0.05). Higher levels of IL-6, IL-8 and TNF-α were found in cell supernatant after stimulation with multimethacrylate (Real Seal) compared to all other sealers tested (P < 0.05). No differences were found comparing epoxy resin-based sealer (AHPlus), single-methacrylate sealer (EndoREZ) and calcium hydroxide-based sealer (Apexit Plus), regardless of the cytokine investigated (all P > 0.05). Conclusions: A SV40 T-Ag-transfected cell line of human pulp-derived cells was established. The methacrylate resin-based sealer (Real Seal) exhibited the greatest cytoxicity and inflammatory potential against immortalized pulp cells compared to an epoxy resin-based sealer (AH Plus), a methacrylate-based sealer (EndoRez) and a calcium hydroxide-based sealer (Apexit).
Keywords: endodontic; inflammatory; root canal; sealer